“No sir, she was not a fool in the field”: Gendered risks and sexual violence in immersed cross-cultural fieldwork - Ross, Karen (The Professional Geographer, 2015)
It is rare to hear about the gendered risks of field work. My experiences with sexual violence with key informants forced me to assume a variety of defensive behaviors, which ran counter to the ways that scholarly discussions of methods tend to emphasize the importance of reducing distance and shifting power away from the researcher in a cross-cultural context. By considering gendered risks, I question the extent to which an idealized male researcher is still viewed as the archetype from which methods are conceptualized and practiced, and the implications are then discussed
Keywords: discipline; ethnographie; genre; pouvoir; ressource en ligne; sciences humaines; thématiques; violences; violences sexistes et sexuelles

Women and media: A critical introduction - Byerly, Carolyn M.; Ross, Karen (John Wiley & Sons, 2008)
Women and Media is a thoughtful cross-cultural examination of the ways in which women have worked inside and outside mainstream media organizations since the 1970s. Rooted in a series of interviews with women media workers and activists collected specifically for this book, the text provides an original insight into women’s experiences. Explains the ways that women have organized their internal and external campaigns to improve media content (or working conditions) for women, and established womenowned media to gain a public voice. Identifies key issues and developments in feminist media critiques and interventions over the last 30 years, as these relate to production, representation and consumption. Functions as both a research case study and a teaching text.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; cinéma; communication; discipline; histoire et politique; médias; projet charge mentale; périodes historiques; ressource en ligne; thématiques; travail